PENGEMBANGAN MODEL LATIHAN KOMBINASI DRIBBLING DAN SHOOTING DALAM PERMAINAN SEPAKBOLA DI SEKOLAH SEPAKBOLA (SSB) UNIBRAW ’82 MALANG - Yulianto Dwi Saputro; Sudarsono; Luthfie Lufthansa (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2018)
Football is the most popular sport in the world. Football players must master the basic techniques of Dribbling and Shooting. From the results of preliminary research at the Unibraw soccer school in Malang, the implementation of the Dribbling and Shooting training model has not applied the effective and efficient principle. This study used research and development method instructional development model from Sadiman (2003).. This study aimed to produce a new product in the form of dribbling and passing combination training models in football game speed and agility with base at Unibraw 82 Football School of Malang. The design of research and development of dribbling and shooting combination models there were stages as follows: (1) determining ideas, by collecting information as the idea base to create a concept; (2) writing media scripts product containing shooting practice model sketches; (3) product evaluation; (4) product revision I; (5) prototype product byshooting training models to small groups as well as large groups; (6) prototype try-out; (7) product revision II; and (8) reproduction. Overall the dribbling and shooting combination training model is feasible to implement as a training models for students at Unibraw 82 football school of Malang.The development of dribbling and shooting combination training models in football game with speed and agility base for students at Unibraw 82 football school of Malang there are 10 dribbling and shooting combination training models, these training models can be applied to add training models for the students of Unibraw 82 football school of Malang to overcome the students saturation in training football and add more variation. Abstrak Sepakbola merupakan cabang olahraga paling populer di dunia.Para pemain sepakbola wajib menguasai teknik dasar Dribbling dan Shooting. Dari hasil penelitian awal di sekolah sepakbola Unibraw ‟82 Malang, penerapan model latihan Dribbling dan Shooting belum menerapkan prinsip efektif dan efisien.Model penelitian ini menggunakan penelitian pengembangan (Research and Development)yaitu model pengembangan instruksional dari Sadiman (2003). Penelitian ini bertujuan untuk menghasilkan sebuah produk baru yang berupa model latihan kombinasi dribblingandpassing dalam permainan sepakbola yang di sekolah sepakbola Unibraw ”82 Malang. Perancangan penelitian pengembangan model kombinasi dribbling and shotting terdapat tahapan sebagai berikut: (1) penentuan ide-ide, dengan mengumpulkan informasi sebagai landasan pemikiran untuk membuat suatu konsep; (2) penulisan naskah media (produk), didalamnya berisi sketsa model-model latihan shooting; (3) evaluasi produk, (4) revisi produk I; (5) produk prototipe, dengan memberikan model latihan shooting kepada kelompok kecil maupun kelompok besar; (6) uji coba prototipe; (7) revisi produk II; dan (8) reproduksi. Hasil penelitian ini adalah 10 model latihankombinasi dribbling and shooting dalam permainan sepakbola, model latihan ini dapat diterapkan untuk menambah variasi model latihan siswa sekolah sepakbola Unibraw “82 Malang sehingga kejenuhan siswa dalam latihan mampu teratasi dengan baik. Kata Kunci: Penelitian Pengembangan, Model Latihan Kombinasi Dribbling and Shootting, Variasi